The Model of Competitive Advantage for Increasing Business Performance in Small and Medium Industries of Woven Fabric (Endek) in Bali Province - I Putu Pratama Adiputra; I Nengah Suardhika; Anik Yuesti (International Journal of Applied Business and International Management, 2023)
One of the Province of Bali's key creative economy sectors that places an emphasis on particular artistic and cultural inventiveness is the woven fabric (endek) sector. The business must make strategic attempts to survive, nonetheless, given the increasingly tough commercial competition and the limited resources available. With the mediating role of competitive advantage, this work intends to further research on the indirect effects of product innovation and market orientation on business performance. In 9 districts and cities throughout Bali Province, this study used a proportional sample technique. Partial Least Square analysis was used to process 78 questionnaires from SME owners of woven fabric (endek). Market orientation can be applied to achieve a competitive advantage, according to the analysis's findings, which can have a stronger impact on business success. The performance of businesses is also directly impacted by market orientation. According to other findings, product innovation has no real impact on how well a company performs. The improvement of business performance in SME woven fabric (endek) in Bali Province, however, can be determined by a product innovation that can produce a competitive advantage. Keywords: Market Orientation, Product Innovation, Competitive Advantage, Business Performance.